POTRET STAGNANSI PERKEMBANGAN KEBIJAKAN BANTUAN UMKM DI KABUPATEN BINTAN - Novi Winarti; Ryan Anggria Pratama (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This research is related to the development of MSMEs in Bintan Regency. Until now, the establishment of business units on the scale of MSMEs in Indonesia has been very rapid. UMKM is expected to be the foundation for future economic growth in Indonesia. Bintan Regency is an area that has huge natural resource potential. In line with the potential of Bintan Regency, the quantity of MSMEs in Bintan Regency also continues to increase. Various policies have been formulated by the government to build a good business climate. However, the large quantity of MSMEs in Bintan Regency does not necessarily make a positive contribution to economic growth in Bintan Regency. This study wants to see how the portrait of the benefits of the MSME assistance policy in Bintan Regency. This research uses descriptive quantitative method. The results of the study prove that the degree of benefit of the MSME assistance policy in Bintan Regency is still relatively low. This is evidenced by 34.6% of respondents who stated that the MSME assistance provided by the government did not provide benefits in business development. This conclusion is also reinforced by the indicators that the development of MSMEs that have received assistance tends to be slow, namely 44.9% of respondents who stated that their business has been running as usual. Inequality of socialization and monitoring carried out by the government also hampers the maximum benefits received by MSME actors in developing their business